The Effect of Chain Writing Method on Students’ Writing Ability of Descriptive Text - Nabilah, Rizkia; As’ari, As’ari; Rahmawati, Eulis (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2023)
Abstract: The objective of this research is to obtain the empirical evidence on the effect of chain writing method on students' writing ability of descriptive text. This research used a quantitative method with quasi-experimental design. The sample of this research is 70 students which is divided into experimental class control class that consist 35 students for each. The results of this research show that the post-test mean score of the experimental class is higher than the post-test mean score of the control class (74 > 56). According to the result of statistic calculation, it is obtained that the score of to = 8.45 > tt = 1.67 in degree of significance 5%. The score of to = 8.45 > tt = 2.39 in degree of significance 1%. It indicates that the value of tobservation is bigger than ttable. tobservation = 8.45 > ttable.= 1.67. tobservation = 8.45 > ttable.= 2.39, so Ho is rejected and Ha is accepted. Thus, it proved that the chain writing method has good effect on the teaching writing of descriptive text and effective to improve students' writing ability of descriptive text.